Switching Strategy Development, Dynamic Model, and Small Signal Analysis of Current-Fed Cockcroft-Walton Voltage Multiplier - Amirhossein Rajaei; Mahdi Shahparasti; Ali Nabinejad; Yousef Niazi; Josep M. Guerrero (IEEE Open Journal of Power Electronics, 2021)
High voltage generation, is one of the main applications of the Cockcroft-Walton voltage multiplier (CWVM), however recently this structure is investigated to be used for high step-up DC-DC applications. This paper discusses dynamic behaviour and small-signal modelling of a CWVM based DC-DC converter and investigates how switching strategy can affect the dynamic performance of the converter. This study firstly presents, a new switching method, the steady-state relations are derived and compared to the conventional switching strategy, which shows that the proposed method equilibrates the voltage and current stress of the switches and decreases the current ripple of the input inductor. Then, the converter is dynamically modelled and analyzed using the pole-zero map. The analysis shows that the proposed switching strategy improves the dynamic behaviour of the converter. The effect of the passive elements on dynamic performance is also discussed. Experimental results are presented for a 160 W prototype to validate the evaluated performance and the dynamic analysis.